The Self-management of Chronic Disease in the Digital Era - Mano, Rita S. (Issues and Development in Health Research Vol. 7, 2021)
This study examines the factors associated with computer use for the self-management of health among individuals diagnosed with chronic diseases in Israel. We distinguish between (a) access to online health information and (b) use of online health services. A geographic representative sample comprising 2008 individuals was contacted. 1406 individuals (67.6%) reported using the computer for health concerns. We seek to show how the digital health information and services among individuals reporting a chronic condition (heart, cancer, diabetes and hypertension) use digital sources to manage their chronic condition (N=225). Our objective is to (a) highlight the extent the self-management among chronically ill is frequent (b) assess that use of online services is not necessarily related to the use of online health information and (c) explore the factors associated with the differential use of online health information and online health services. Using a series of logit regression models it is shown that chronic disease increases access to online health information but its effect of use of online health services is specific to (a) type of chronic disease, i.e., heart condition and (b) type of provided service, i.e., medical updates. These results indicate that while computer use increases the odds for higher empowerment this may not necessarily lead to higher use of online health services provided by the healthcare provider among individuals diagnosed with chronic disease decreasing the likelihood for better self-management. Implications for health policy are discussed